Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang di Pasar Reok Kabupaten Manggarai Nusa Tenggara Timur Tahun 2020 - Jomi, Maryunus; Widodo, Sugeng; Hariani, Ermatry (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2020)
Traditional markets are still very important centers of economic activity for some people in Indonesia. In the market, someone can distribute the products they produce for sale, with this activity the sellers can get income every day.